2004
DOI: 10.1158/1078-0432.ccr-03-0484
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of KLF4 Is Associated with an Aggressive Phenotype in Early-Stage Breast Cancer

Abstract: Purpose: The Krü ppel-like transcription factor KLF4/ GKLF induces both malignant transformation and a slowgrowth phenotype in vitro. Although KLF4 expression is increased in most cases of breast cancer, it was unknown whether these cases represent a distinct subtype with a different clinical outcome.Experimental Design: We examined expression of KLF4 by immunostaining 146 cases of human primary infiltrating ductal carcinoma of the breast. Staining patterns were correlated with clinical outcome and with establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(189 citation statements)
references
References 45 publications
11
175
1
2
Order By: Relevance
“…Representative results of two independent data sets characterized by large population sizes (Miller et al, 2005;Ivshina et al, 2006;Richardson et al, 2006;Finak et al, 2008) are shown in Figure 1a (KLF4 expression levels in normal versus breast carcinoma; P ¼ 5.4EÀ4, 7.0EÀ3) and 1b (KLF4 expression levels in breast cancers classified by grade; P ¼ 8.0EÀ11, 2.6EÀ10). Earlier reports have shown that 70% of breast carcinomas have elevated KLF4 expression and that increased nuclear staining for KLF4 is associated with a more aggressive phenotype (Foster et al, 2000;Pandya et al, 2004). Inconsistencies between the results obtained from the Oncomine database and earlier reports may be due to the genetic or epigenetic context of breast cancer tissues.…”
Section: Resultsmentioning
confidence: 94%
“…Representative results of two independent data sets characterized by large population sizes (Miller et al, 2005;Ivshina et al, 2006;Richardson et al, 2006;Finak et al, 2008) are shown in Figure 1a (KLF4 expression levels in normal versus breast carcinoma; P ¼ 5.4EÀ4, 7.0EÀ3) and 1b (KLF4 expression levels in breast cancers classified by grade; P ¼ 8.0EÀ11, 2.6EÀ10). Earlier reports have shown that 70% of breast carcinomas have elevated KLF4 expression and that increased nuclear staining for KLF4 is associated with a more aggressive phenotype (Foster et al, 2000;Pandya et al, 2004). Inconsistencies between the results obtained from the Oncomine database and earlier reports may be due to the genetic or epigenetic context of breast cancer tissues.…”
Section: Resultsmentioning
confidence: 94%
“…KLF4 overexpression becomes evident at the stage of ductal carcinoma in situ, indicating that, similar to squamous cell carcinoma, this represents an early event in breast cancer progression 59 . Furthermore, nuclear localization of KLF4 was found to be a predictor of poor outcome of breast cancer 60 . In contrast to many other cancer types, TP53 is often not mutated in sporadic breast cancer.…”
Section: Klf4 As An Oncogenementioning
confidence: 98%
“…Current studies in carcinogen-esis have revealed that KLF4 can function as both tumor promoter and tumor suppressor depending on tissue type and cellular context [241]. The oncogenic effect of KLF4 has been reported in breast and squamous cell carcinoma [243][244][245][246][247], while its tumor suppression role was reported in various types of cancers such as colon cancer [248,249]. It was demonstrated that KLF4 is a fast turnover protein, whose turnover-half life is governed by the ubiquitin-proteasome system [250,251].…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%